The hero cult : a spectacle of world history that changed civilization - Haarmann, Harald; LaBGC (Harrassowitz Verlag, 2021)
"With their patriarchal structure and clear hierarchy, the Indo-Europeans from the Eurasian steppe took advantage or their warrior caste and won the fusion process with the ancient Europeans. First slowly over generations then rapidly, life in Old Europe changed from a peaceful egalitarian system to a patriarchal class system with the important class of warriors. What the newcomers maintained from the Old European order were the goddesses. The veneration of goddesses continued to be a vital part of life and additionally, goddesses were now seen as patrons to the warriors, accompanying and protecting them on their way to become heroes. One of these pre-Greek goddesses stands out among all the other daughters of the Goddess of Old Europe, and this is Athena. The interaction of this pre-Greek goddess with the Indo-European heroes will be highlighted in particular"--Page 4 of cover.